Rancang Bangun Sistem Pemberian Nutrisi AB Mix Otomatis untuk Hidroponik Sistem Wick Berbasis IoT - Muhammad Tryora Inzaghi; I Wayan Agus Arimbawa; Ari Hernawan (Journal of Computer Science and Informatics Engineering (J-Cosine), 2023)
Hydroponics is agricultural cultivation using water as a medium to replace soil. One of the simplest hydroponic systems is the wick system. The wick system is a passive system, where water is only stored in a container and there are no moving parts. The hydroponic growth of the wick system is very influential on the nutrient solution that is commonly used in hydroponic wick systems, namely AB mix nutrition. Providing AB Mix nutrient concentration of 1000-1300 ppm is the best concentration. The provision of nutrition is currently carried out by monitoring water conditions manually in the hydroponic system. This can cause monitoring not to be carried out so that it can have an impact on plant growth that is less than optimal. Therefore, the authors conducted research to design an automatic AB mix nutrition system for IoT-based hydroponic wick systems. This research makes it possible to provide AB mix nutrition automatically by utilizing a water level sensor, TDS (Total Dissolve Solid) sensor, water pump and using the MQTT data communication protocol. This study uses hardware testing to test all sensors such as TDS sensors, water level sensors and relays in terms of functionality. The results show that everything is working properly reading the changes that have occurred. After that, testing the entire system was carried out by making several scenarios to see the system's reaction to the scenarios that were made. The system can control the nutrient content of plants with the amount of nutrient content according to the needs of the pakcoy plant, which is 1000-1300 ppm. When the plants lack nutrients, the system will pump the nutrients into the hydroponic container to meet the nutritional needs of the plants.